A Theoretical Assessment of Antioxidant Capacity of Flavonoids by Means of Local Hyper–Softness - Mascayano-Collado, C (Elsevier B.V., 2018)
A theoretical reactivity descriptor to estimate local reactivity on molecules was tested to assess the antioxidant capability of some flavonoids. It was validated by comparison with experimental precedents published already by Firuzi et al. (2005). The aforementioned reactivity index is called local hyper-softness (LHS). This parameter was applied on HO- substituent groups on the same set of flavonoids within each subclassification: flavones (apigenin and baicalein), flavonols (fisetin, galangin, 3–OH flavone, kaempferol, myricetin, and quercetin), flavanones (hesperetin, naringenin, taxifolin) and isoflavones (daidzein and genistein). Experimental values of both techniques, ferric reducing antioxidant power (FRAP) and anodic oxidation potential (Eap) were retrieved from Firuzi et al. (2005) with the purpose of validating the calculated LHS values. Excepting myricetin, the LHS values of all these compounds matched in a similar order relationship experimentally obtained by means of Eap and FRAP from Firuzi et al. (2005). Our results revealed that LHS is a suitable theoretical parameter to get an insight concerning to the antioxidant capacity of these compounds, in particular, LHS allows explaining experimentally obtained values of FRAP along with Eap values in terms of reactivity of HO- substituent groups belonging these molecules theoretically computed without including experimental parametes. © 2017 King Saud University